Pengembangan Augmented Reality Berbasis Android Dalam Pembelajaran Ipa SMP/mts pada materi sistem pencernaan - Santika, Afrillesia; Susilawati, Susilawati (SAINFIS: Jurnal Sains Fisika, 2024)
The purpose of this research was to produce Android-Based Augmented Reality in Science Learning on Digestive System Material at Junior High School that met valid and practical criteria, and to find out students' responses to media. The type of research used is research and development (research and development) the development model of Sugiyono (2019). This research step is limited to the seventh step, namely product revision, this is due to the limitations of the researcher. The data in this study used qualitative and quantitative data with data collection techniques used were observation, interviews, questionnaires and documentation using data analysis techniques used were descriptive qualitative and descriptive quantitative. The results of the validity of the android-based augmented reality product have been declared very valid based on the results of validation by media experts obtaining a value of 82%, learning material experts declared valid by obtaining a value of 78% and by linguists obtaining a value of 90% very valid. The level of practicality by the teacher which is stated to be very practical to use for students in learning by obtaining a value of 94%. The response was very good from 25 students of class VIII at Islamic State Junior High School 3 Pekanbaru by obtaining a score of 90% for android-based augmented reality in science learning on the material of the human digestive system at Junior High School. Based on expert judgment and limited tests, android-based augmented reality in science learning on digestive system material at Junior High School is feasible to use in science learning